Monomorphic pattern for BMPR1B gene in prolific Alpine x Beetal and Saanen x Beetal goats - Shweta Sahoo,; Amritanshu Upadhyay,; Rani Alex,; S.K. Rathee,; G.R. Gowane, (Journal of Livestock Biodiversity, 2025)
The present study was aimed to delineate genetic variability of Bone Morphogenetic Protein Receptor type 1B(BMPR1B) or FecB gene in Alpine x Beetal and Saanen x Beetal crossbred goats maintained at ICAR-NationalDairy Research Institute, Karnal, Haryana. The mutation present at (Q249R) in BMPR1B gene induces earlymaturity of ovarian follicles by increasing the sensitivity of the follicles to FSH leading to release of more eggsper cycle which increases fecundity and forms the basis of marker assisted selection. Genomic DNA was extractedfrom blood samples of 88 animals from both the breeds and one set of primers were used to amplify a 140bpfragment of FecB gene. The amplified fragments were digested using Ava II enzyme. All the animals under studywere found to be non-carriers for FecB mutation evidenced by the absence of any polymorphism observed afterPCR-RFLP suggesting no apparent association of this mutation with fecundity in Alpine x Beetal and Saanen xBeetal crossbred goats.